2012
DOI: 10.1111/1365-2435.12000
|View full text |Cite
|
Sign up to set email alerts
|

Staying tuned: grasshoppers from noisy roadside habitats produce courtship signals with elevated frequency components

Abstract: Summary1. Anthropogenic noise is known to affect acoustic signal production in birds, frogs and mammals. These animals use different mechanisms to adjust their signals to elevated background noise levels (increase in signal amplitude, shift to higher frequencies, etc.). Previous studies have concentrated on behaviourally plastic changes in signal production as a result of elevated background noise levels. To our knowledge, long-term effects of anthropogenic noise on signal production have not yet been investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 34 publications
5
90
1
2
Order By: Relevance
“…Subjects were transferred to the laboratory and recorded using a Bruel & Kjaer 4939 microphone (Naerum, Denmark) in combination with an UltraSoundGate 116 recording system (Avisoft Bioacoustics, Berlin, Germany) and processed by Avisoft-SASLab Pro bioacoustics software 4.3 (Avisoft Bioacoustics, Berlin, Germany; see Lampe et al 2012 for details on the recording setup). We analyzed three songs per individual.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were transferred to the laboratory and recorded using a Bruel & Kjaer 4939 microphone (Naerum, Denmark) in combination with an UltraSoundGate 116 recording system (Avisoft Bioacoustics, Berlin, Germany) and processed by Avisoft-SASLab Pro bioacoustics software 4.3 (Avisoft Bioacoustics, Berlin, Germany; see Lampe et al 2012 for details on the recording setup). We analyzed three songs per individual.…”
Section: Methodsmentioning
confidence: 99%
“…Shieh et al [12] compared the calling behaviour of the cicada Cryptotympana takasagona in noisy and quiet urban parks, finding positive correlations between noise levels and both call frequency and chorusing. Lampe et al [13] found that male bow-winged grasshoppers (Chorthippus biguttulus) collected from noisy roadsides sang with a greater low-frequency component than males collected from paired quiet areas nearby. As male singing was recorded in the absence of noise stimuli in anechoic chambers, the differences are unlikely to be the consequence of behavioural plasticity, but instead may result from longer term adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the quality of a given signal is not necessarily positively correlated with intensity. In addition, further sound sources such as abiotic (Brumm and Slabbekoorn, 2005;Reichert and Ronacher, 2015) or even anthropogenic noise (Lampe et al, 2012(Lampe et al, , 2014Schmidt et al, 2014) may impede signal representation and recognition. Crickets, bushcrickets and grasshoppers are known to employ several processing tools to reduce the detrimental effects of masking and noise (EinhĂ€upl et al, 2011;Schmidt and Römer, 2011;Neuhofer and Ronacher, 2012;Hildebrandt et al, 2015), most prominently by forward masking, selective attention, formation of acoustic hemispheres and stream segregation (Pollack, 1986;Schul and Sheridan, 2006;Triblehorn and Schul, 2009;Schmidt and Römer, 2011).…”
Section: Discussion Signal Representation and Cues For Decision Makingmentioning
confidence: 99%